Endovascular thrombectomy (EVT) of an atherosclerotic plaque masquerading as thrombus in a large vessel occlusion (LVO) stroke - Muda, Ahmad Sobri; Md Noh, Mohamad Syafeeq Faeez; Abdul Rahim, Ezamin; Mohd Nasir, Noor 'Ain; Kamis, Mohd Fandi Al Khafiz (Longe Medikal, 2023)
A 37-year-old male with a history of hypertension and hyperlipidaemia presented with acute stroke at 4.5 hours, with a NIHSS score of 4. MRI revealed a left basal ganglia infarct, with a left M1 segment large vessel occlusion (LVO) and suspicious plaque enhancement on the black blood sequence measuring about 1.5 mm in length Figure 1. Angiography with cone beam CT (VasoCT) showed suspicious ICAD, with short segment stenosis at the M1 segment. Complete recanalization (TICI 3) was achieved after three passes via thrombectomy, using the ˜Solumbratechnique. A pale, firm lesion was primarily retrieved, accompanied by minimal clots. Patient was discharged at day 10 with a NIHSS score of 1.